The relationship between the attitude towards physical exercise and the sports consumption demand of the group with a relatively low level of education: a test of the mediating effect of the amount of physical exercise - Hu, Shunding; Feng, Xiaosu (Frontiers in Psychology, 2025)
ObjectiveExplore the relationship between the attitudes towards physical exercise sports consumption demands among groups with lower education levels, and test the mediating effect of the amount of physical exercise.MethodsA combination of stratified sampling and convenience sampling was adopted to select 762 individuals who had not received higher education from non-urban areas of Dalian as participants, covering groups with educational backgrounds of junior school or below and senior school (technical secondary school, technical school). The Exercise Attitude Scale, Physical Exercise Rating Scale, and Sports Consumption Demand Scale were used to investigate the participants’ attitudes towards physical exercise, the amount of physical exercise, and sports consumption demands. SPSS 25.0 and AMOS 23.0 software were used to explore the relationships among variables through inter-group comparative analysis, correlation analysis, regression analysis, and mediating effect tests.ResultsThere is a significant positive correlation between the attitude towards physical exercise, the amount of physical exercise, and the sports consumption demand (p < 0.01). After controlling for relevant confounding factors, the attitude towards physical exercise could positively predict the sports consumption demand (p < 0.01). Except that the relationships between behavioral cognition, emotional experience, and the sports consumption demand were not significant (p > 0.05), the positive predictive effects of the remaining dimensions were significant (p < 0.05). The mediating effect test indicated that the amount of physical exercise played a mediating role between the attitude towards physical exercise and the sports consumption demands (β = 0.003, p = 0.029).ConclusionThere is a significant positive correlation between the attitude towards physical exercise and the sports consumption demands among people with lower education levels, and the amount of physical exercise plays a mediating role in the relationship between the two. The conclusions have improved the “attitude → behavior → consumption” theory, providing a basis for the formulation of policies by relevant departments.